ANTI-CRISIS RESISTANCE OF ENTERPRISES AND SECOND ASSESSMENT IN UNSTABLE CURRENT CONDITIONS (Development Service Industry Management, 2024)
The article is devoted to the research of author's methods and approaches of experts to assess the stability of economic entities to identify their key features, sequence of conduct and shortcomings in order to develop a methodological approach to assessing the anti-crisis stability of the enterprise in the future. The essence, directions, functional components and results of evaluation of various types of stability (financial, economic, anti-crisis) are analyzed. Taking into account the peculiarities of the process-functional approach of management of the organization, it is proposed to assess the anti-crisis stability within the resource-management direction, since it takes into account both the level of utilization of the resource potential of a particular industrial enterprise and the quality of its management activities, from which, in the first place, survival and sustainable development in the future. According to the results of the analysis of experts' opinions and expert opinion, a rating of ten basic functional components was formed and six of them recommended for use (financial, profitability, liquidity, techno-technological, personnel, organization of production), which ranked the highest in the rating. The assessment of the company's crisis-resistant sustainability is recommended to be carried out in two groups of functional components (financial, economic, and production management). The necessity of using economic factor analysis for the identification and selection of factors of influence and the formation of the system of indicators by selected functional groups are substantiated. For a comprehensive and comprehensive study of the state of affairs at the enterprise, it is proposed to use a combination of three types of economic factor analysis at the same time - technical, financial, and socio-economic.Еconomic factor analysis makes it possible to comprehensively and comprehensively describe the object of research, assess the impact of individual factors on the resulting indicator, identify hidden variables that are responsible for the presence of linear statistical correlations. As a result of the use of economic factor analysis, an economic-mathematical model can be built, which will describe and make it possible to evaluate the influence of individual factors on the general level of anti-crisis stability of an industrial enterprise. The final stage is the development and adoption of management decisions and control measures regarding the most important factors that negatively affected the results of the enterprise.
Keywords: stability; anti-crisis enterprise stability; directions of evaluation; functional components; economic factor analysis; system of indicators